2016
DOI: 10.1111/ens.12180
|View full text |Cite
|
Sign up to set email alerts
|

β‐Ionone as putative semiochemical suggested by ligand binding on an odorant‐binding protein of Hylamorpha elegans and electroantennographic recordings

Abstract: Currently, odorant‐binding proteins (OBPs) are considered the first filter for olfactory information for insects and constitute an interesting target for pest control. Thus, an OBP (HeleOBP) from the scarab beetle Hylamorpha elegans (Burmeister) was identified, and ligand‐binding assays based on fluorescence and in silico approaches were performed, followed by a simulated binding assay. Fluorescence binding assays showed slight binding for most of the ligands tested, including host‐plant volatiles. A high bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…These genes have been characterized in whole genome level only the flour beetle T. castaneum [37]. Several species have been identified partly by RNA-seq, such as two bark beetles (I. typographus and D. ponderosae) [20], two leaf beetles (P. aenescens and P. maculicollis) [27], scarab beetle Hylamorpha elegans [50], and a leaf beetle C. lapponica [49]. In the present study, we identified the chemosensory gene families at whole genome level in a pair of blister beetles (Meloidae: Hycleus) in the Meloidae and provided the evolution analysis of chemosensory genes within Coleoptera groups.…”
Section: Discussionmentioning
confidence: 99%
“…These genes have been characterized in whole genome level only the flour beetle T. castaneum [37]. Several species have been identified partly by RNA-seq, such as two bark beetles (I. typographus and D. ponderosae) [20], two leaf beetles (P. aenescens and P. maculicollis) [27], scarab beetle Hylamorpha elegans [50], and a leaf beetle C. lapponica [49]. In the present study, we identified the chemosensory gene families at whole genome level in a pair of blister beetles (Meloidae: Hycleus) in the Meloidae and provided the evolution analysis of chemosensory genes within Coleoptera groups.…”
Section: Discussionmentioning
confidence: 99%
“…High binding affinity for beta-ionone was also demonstrated in OBPs of many other insect species, such as H . armigera , Sogatella furcifera , and Microplitis mediator [3436]. PameOBP2 also had high binding affinities for tetradecane and geranylacetone, two cashew apple juice volatiles [37], with Ki values of 0.96 and 6.97 μM, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This result further supports the view that OBPs are not just simple, general solubilizers that act as transporters for odorants but also play a vital role in the perception of different kinds of chemicals in the environment (Pelosi et al, 2006;Swarup et al, 2011). An OBP in Hylamorpha elegans showed a high binding affinity to β-ionone (Venthur et al, 2016), a volatile compound derived from plant carotenoids (Simkin et al, 2004). …”
Section: Discussionmentioning
confidence: 99%